PERAN IBU BEKERJA DALAM MENUMBUHKAN PERILAKU GEMAR MEMBACA SEJAK DINI PADA ANAK: The Role of Working Mothers in Cultivating a Love for Reading in Children from an Early Age - Isna Fistiyanti (IJAL (Indonesian Journal of Academic Librarianship), 2024)
The research conducted in Surabaya aimed to describe the efforts of working mothers in fostering reading habits in their children. The study population consisted of working mothers with children from preschool age to early elementary school. Respondents were selected through purposive sampling with criteria of working in the formal sector, having children aged 2-7 years, and being either married or single parents. Data were collected through surveys using semi-open questionnaires and probing techniques to gain in-depth information about the unique efforts made by respondents. Primary data came from the questionnaires and probing, while secondary data were obtained from various literature sources. Observations were also conducted to observe related phenomena. Both quantitative and qualitative analyses were used to enrich the research results. The study concluded that the role conflict of working mothers affects the division of time between work and household duties, hindering efforts to foster children's reading interest. Although working mothers strive for balance, their main focus often remains on household chores. Children's reading activities are done in between busy schedules, not at specially scheduled times. Mothers with flexible working hours, such as lecturers or teachers, are better able to schedule their children's reading time. This research emphasizes the importance of time flexibility in supporting children's education at home and the need for effective strategies to support children's reading interest amidst the busyness of working mothers.